Between (Pseudo)Silence and Noise – the Perceptive Status of Music in the Lo-Fi Environment: The Case of Contemporary Shopping Malls - Makomaska, Sylwia (Interdisciplinary Studies in Musicology, 2022)
Modern shopping malls are interesting examples of lo-fi soundscapes where the recipi- ents experience diverse auditory phenomena. One of the key factors organising the space is so called programmed music provided by audiomarketing companies. To what extent can this specific context change the perception of music, noise, and silence? Is the imposed music viewed from the perspec- tive of the listeners as music or perhaps noise? These questions shape the discussion on the per- ceptive status of music in lo-fi environments. More than 200 participants (between 18–30) took a soundwalk in one of the shopping malls in Warsaw where audiomarketing strategy is implemented. They were asked to record the characteristic places, to fill in the questionnaire of observation and evaluation and to write a narrative essay once the soundwalk was finished. As a result, an exten- sive set of qualitative and quantitative data was obtained, which was then subjected to a multi-stage analysis: thematic (text data), statistical (quantitative data), auditory and spectral (audio files). The results show that in the case of shopping malls the line between silence, music and noise is blurred because imposed music can become both a part of cacophonic experience and “silence zones”. During the soundwalks, 27% of the participants (n = 57, N = 208) declared they did not experience silence and 75% of the participants (n = 151) identified varied “silence zones”, even with the programmed music in the background. These observations lead to the problems of desensitisation and habituation as possible long-term consequences of noise pollution.